Analisis Sistem Informasi Akuntansi Penggajian Karyawan Pada PT. Star Rubber Kecamatan Jujuhan Kabupaten Bungo Provinsi Jambi (International Forum of Researchers and Lecturers, 2023)
Analysis of employee payroll accounting information systems should be carried out effectively and required relevant information and a system, namely an accounting information system as a means of communication which can later be used for the needs of company management. Likewise things at PT. Star Rubber Jujuhan Bungo Jambi Regency where employee payroll accounting is very important. The purpose of this study was to determine the payroll accounting information system for employees at PT. Star Rubber, obstacles in employee payroll accounting information systems and efforts to overcome obstacles in employee payroll accounting information systems at PT. Star Rubber. This study used qualitative research methods. Data were obtained from subjects in the study including the Director, Expenditure Treasurer and employees regarding the payroll system of PT. Star Rubber Jujuhan and Employees of PT. Star Rubber. The results showed that the Employee Payroll Accounting Information System at PT. Star Rubber has been designed to support the achievement of company goals and the creation of good internal control. In addition, the payroll and remuneration system is also designed to ensure that employees' salaries and wages are paid. While the related functions at PT. Star Rubber is a staffing function that is held by the personnel department, the function of recording employee attendance times is held by the timekeeper, the function of making payroll and wages is handled by the personnel section, the cashier function, and the function of paying salaries and wages is authorized by the personnel and cashier section.